The Influence of Technology on Economic Growth in Indonesia in 2010-2020 - Nursari, Ayu (Jurnal Jejama Manajemen Malahayati, 2023)
This study aims to analyze the effect of R&D investment, the volume of e commerce transactions, and e-commerce companies employee on economic growth in Indonesia for the period 2010Q1 – 2020 Q4. The analytical method used in this study is OLS (Ordinary Least Square) anda method using time series data in the form of quarterly from 2010 to 2020. In conducting this research the author uses the help of the E-views 9 analysis tool. The results of this study are that the variables of R&D investment, e-commerce companies employee, and the volume of e-commerce transactions have a partial or joint effect on economic growth in Indonesia in 2010 Q1 to 2020 Q4. This research is limited by several factors, among others; R&D investment, e-commerce companies employee, and volume of e-commerce transactions. The results obtained from this research are expected to be one of the references in making policy directions based on the data presented to adjust the right policies, especially to achieve economic digitization in Indonesia.